(untitled) (Fiep Bulletin - online, 2015)
Is is evident that sport is today a true social phenomenon with marked repercussion in the life of peoples. As a result of human exigencies which represent in each nation a reflex of is social structure and reach paroxysm due to the fight it creates and although separating itself progressively from its fundamental aims, sport remains, in spite of everything, on the first plan of present day interests.